Simulasi Numerik Penempatan Shark Fin Vorteex Generator dengan Susunan Straggered pada Dinding Kiri dan Kanan Bus Penumpang - Tiara Pradina Putri; Wawan Aries Widodo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this study, evaluating the effects of the use of vortex's shark fin generator (SFVG) on passenger buses' aerodynamics used numerical analysis. Studies show that buses with SFVGS show a slightly lower maximum rate (896.94 m/s) than buses with no SFVG (933.61 c.e. /s), indicating that SFVG does not have an effect on increased air speed. The coefficient analysis of drag (CD) shows a significant decline on buses with SFVG (CD averages about 0.6165738) compared to buses without SFVGS (CD around 0.72478044), signifying a reduction in drag style. Although SFVG increases the elevator coeffluent (cl) on a bus (cl approximately 0.018557634), this increase is small and affects the stability of vehicles. The pressure on the front of the bus with SFVG (204.13 pa) is slightly lower than a busload (209.16 pa), with a potential effect on the lift and stability of the entire bus. Studies highlight the need for further optimization to achieve the balance between the aerodynamic efficiency and the stability of vehicles, and the need for advanced research to understand the overall effect of the SFVG on the energy efficiency and aerodynamic performance of buses.